Research and Design of Embedded uC/OS-II Network Storage System - Xiaowei Zhang; Fensu Shi (Institute of Advanced Engineering and Science, 2013)
This article describes a network storage system, which is developed on the embedded system platform. It uses the open-source embedded real-time operating system kernel uCOS-II. Because the kernel is far from complete, such as the lack of a file system, device management, network protocol stack, graphical user interface, but it is small and open source.We extended its functions, such as to add LwIP network protocol stack, IDE hard drive, DM9000 NIC driver, NOR FALSH drive and a file system that supports large-capacity memory and etc, making it an embedded network storage system based on uCOS-II. DOI: http://dx.doi.org/10.11591/telkomnika.v11i4.2373